2001
DOI: 10.1097/00005053-200107000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Correlates of Helplessness, Hopelessness, and Well-Being in Schizophrenia

Abstract: Persons with schizophrenia are widely recognized to experience potent feelings of hopelessness, helplessness, and a fragile sense of well-being. Although these subjective experiences have been linked to positive symptoms, little is known about their relationship to neurocognition. Accordingly, this study examined the relationship of self-reports of hope, self-efficacy, and well-being to measures of neurocognition, symptoms, and coping among 49 persons with schizophrenia or schizoaffective disorder. Results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 32 publications
2
30
0
1
Order By: Relevance
“…Results are largely consistent with the results of previous studies of the correlates of hope [22][23][24][25][26][29][30][31]. Both the expectation of success in the future and the expectation of being able to persist were linked to lesser levels of stigma, fewer symptoms, lesser anxiety, and lesser preference for avoidant forms of coping.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results are largely consistent with the results of previous studies of the correlates of hope [22][23][24][25][26][29][30][31]. Both the expectation of success in the future and the expectation of being able to persist were linked to lesser levels of stigma, fewer symptoms, lesser anxiety, and lesser preference for avoidant forms of coping.…”
Section: Discussionsupporting
confidence: 89%
“…Experiencing symptoms has been suggested to be naturally demoralizing and leads to fewer positive expectations for the future. At the psychological level, lack of hope has been linked with a generally avoidant coping style and a vulnerability to feeling anxious when facing social situations or other stressors [26,[29][30]. Implied here is that as persons unsuccessfully cope with stressors, they may begin to anticipate failure, increasingly fear embarrassment, and see fewer reasons to persevere.…”
Section: Introductionmentioning
confidence: 99%
“…Even after controlling for negative symptoms, one prospective study found that when participants were faced with difficulties, their dysfunctional beliefs about giving up significantly predicted poor rehabilitation outcome [8]. Negative beliefs about the self have also been linked to other behaviors that may compromise vocational function, including avoidant coping [9,18], poor participation in treatment [19], and generally poor social function [7,20].…”
Section: Introductionmentioning
confidence: 99%
“…Parker et al (2008), for example, found a relationship between a correlate of intelligence (brain size) and apparent indicators of psychological well-being (e.g., "feeling useful"). In a sample of schizophrenic adults, Lysaker et al (2001) found small correlations between tests of specialized cognitive abilities and the well-being subtest score of the Attitude Questionnaire. Plescia-Pikus et al (1988) found higher intelligence in both adult children of alcoholics who reported high well-being and controls, compared to adult children of alcoholics who reported low well-being.…”
Section: Distal Causes Of Intelligence-based Differences In Psychologmentioning
confidence: 89%